2012
DOI: 10.3732/ajb.1100235
|View full text |Cite
|
Sign up to set email alerts
|

Variation in intra‐annual wood formation, and foliage and shoot development of three major Canadian boreal tree species

Abstract: The results show that both the timing of growth processes and environmental dependences differ among co-occurring species, thereby leading to different adaptive capability of these boreal tree species to climate change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 51 publications
3
37
0
Order By: Relevance
“…Furthermore, a study from Zhai et al . () indicated that when precipitation had a positive effect on growth, the temperature's impact on growth was less than that of tree water status. However, the requirements for both early and late wood formation (during the post‐growth phase) have varying temperature and water availability requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study from Zhai et al . () indicated that when precipitation had a positive effect on growth, the temperature's impact on growth was less than that of tree water status. However, the requirements for both early and late wood formation (during the post‐growth phase) have varying temperature and water availability requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Both cambium activity and the onset of xylem formation occurred before budburst in the two species, which is consistent with other boreal (Zhai et al ., ) and European (Rossi et al ., ) conifers. The start of wood formation before budburst thus indicates an alternative source of energy and carbon skeletons during this period (Begum et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The trees currently growing at the sites have genetically adapted to the local environmental and climate conditions, and would not be able to fully adapt to future climatic conditions considering the rate of changes and the pace of genetic selection [34], [47]. However, they can demonstrate some growth plasticity to respond to climate warming such as early onset of xylem cell production [48], [49], spring early flowering, budburst, and shoot extension [49], [50]. As the next generation develops acclimation of seeds to new climatic environment and selection of best adapted genotypes will contribute to a better response to the changing climate.…”
Section: Discussionmentioning
confidence: 99%